Sensory Processing Abnormalities in Community-Dwelling Older Adults with Cognitive Impairment: A Mixed Methods Study. (5th January 2022) - Rhodus, Elizabeth K.; Hunter, Elizabeth G.; Rowles, Graham D.; Bardach, Shoshana H.; Parsons, Kelly; Barber, Justin; Thompson, MaryEllen; Jicha, Gregory A.
Mild cognitive impairment (MCI) or dementia often leads to behavioral and psychiatric symptoms of dementia (BPSD). Sensory processing abnormalities may be associated with BPSD. The purpose of this study was to explore relationships among sensory processing, behavior, and environmental features within the homes of people with MCI or dementia. This project used mixed methods to assess participants' sensory processing, care partner perspectives on behaviors, and in situ observations of the home environment. Nine participants with cognitive impairment (MCI n = 8, early dementia = 1) and their care partners were included. Seven participants with cognitive impairment were reported to have abnormal sensory processing. Findings suggest that unique environmental adaptations, tailored to personal and sensory preferences for each participant, were associated with a decreased level of behavioral disruption during the observation periods. Implementing sensory-based approaches to maximize environment adaptation may be beneficial in reducing disruptive behaviors for adults with cognitive impairment.